The Effectiveness of The Yaumul Talaqqi Model Teacher Development Program to Increase The Performance of Islamic Regional Education Teachers - Aulia Istikomah; Alfi Zahrotuz Zakiyyah; Ilma Afrida Wafiroh; Awalu Briliana Famila; Aflah Muzakiyatul Husna; Ragil Dian Putri (CV. Bimbingan Belajar Assyfa, 2024)
This study aims to analyze the effectiveness of a teacher development program in improving the performance of Islamic Education (PAI) teachers at Al Furqon Foundation in Ponorogo. A quantitative approach was used, involving 39 PAI teachers selected purposively as respondents. The independent variable (X) is the effectiveness of the teacher development program, while the dependent variable (Y) is the performance of PAI teachers, measured through pedagogical, professional, social, and personal aspects. Data were collected using validated and reliable questionnaires as well as performance observation sheets. Data analysis included linearity tests, paired t-tests, and the coefficient of determination. The results showed a significant linear relationship between the effectiveness of the development program and teacher performance, with a determination coefficient (R² = 0.532) indicating that 53.2% of the variation in performance improvement can be explained by the effectiveness of the development program.